A uniformly decorated and photostable polydopamine–organic semiconductor to boost the photoelectrochemical water splitting performance of CdS photoanodes. Issue 5 (21st January 2021) - Ruan, Mengnan; Guo, Dandan; Jia, Qixiang
Abstract : Photoelectrochemical (PEC) water splitting to produce renewable H2 fuel by storage of solar energy has attracted increasing attention as it could reduce carbon footprint and solve the global consumption growth. Abstract : Photoelectrochemical (PEC) water splitting to produce renewable H2 fuel by storage of solar energy has attracted increasing attention as it could reduce carbon footprint and solve the global consumption growth. Herein, a photostable polymer polydopamine (PDA) was introduced to enhance the PEC performance by forming a uniform inorganic–organic hybrid heterostructure with CdS. The organic semiconductor PDA not only forms a strong coordinate bond to facilitate the transfer of electrons, but also acts as a passivation layer, contributing to improve the stability of the photoelectrode. A photocurrent density of 1.08 mA cm −2 was achieved for CdS/1PDA, which was about 2.4 times that of bare CdS at 0.28 V vs. RHE, and CdS/1PDA featured a reasonable photocurrent stability compared with bare CdS. The Co–Pi co-catalyst, as a hole acceptor, further prohibited charge recombination and promoted the water oxidation kinetics. The photocurrent density of CdS/1PDA/5Co–Pi was up to 2.68 mA cm −2 (0.28 V vs. RHE), which was 5.7 and 2.5 times higher than that of bare CdS and CdS/1PD, respectively. The strategy provides a beneficial insight to design an inorganic–organic uniform heterostructure for the enhancement in PEC performance.